1997
DOI: 10.1109/3.631287
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication, and performance of infrared and visible vertical-cavity surface-emitting lasers

Abstract: Abstract-This paper discusses the issues involving the design and fabrication of vertical-cavity surface-emitting lasers (VCSEL's). A review of the basic experimental structures is given, with emphasis on recent developments in distributed Bragg reflectors, gain media, as well as current and optical confinement techniques. The paper describes present VCSEL performance, in particular, those involving selective oxidation and visible wavelength operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(79 citation statements)
references
References 101 publications
1
78
0
Order By: Relevance
“…High quality VCSELs can be realized using the GaAs/ ͑AlGa͒As material system where the excellent matching of the materials' lattice constants, the high refractive index contrast, and the mature growth technology offer high quality Bragg mirrors. 2 However, emitters at telecommunication wavelengths today are often InP-based ͑InGa͒͑AsP͒ structures, which cannot be grown on GaAs due to the high lattice mismatch. Possible GaAs-based alternatives include the dilute nitrides, 3 InAs/ GaAs quantum dots 4 and, as is discussed here, Ga͑AsSb͒ quantum wells where room temperature VCSEL operation was already demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…High quality VCSELs can be realized using the GaAs/ ͑AlGa͒As material system where the excellent matching of the materials' lattice constants, the high refractive index contrast, and the mature growth technology offer high quality Bragg mirrors. 2 However, emitters at telecommunication wavelengths today are often InP-based ͑InGa͒͑AsP͒ structures, which cannot be grown on GaAs due to the high lattice mismatch. Possible GaAs-based alternatives include the dilute nitrides, 3 InAs/ GaAs quantum dots 4 and, as is discussed here, Ga͑AsSb͒ quantum wells where room temperature VCSEL operation was already demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…But there is also one new feature which has not been included in the previous model because of its negligible impact on properties of the above VCSELs and which has happened to be extremely important in the GaInP/AlGaInP one. In the AlGaInP compounds, the crossover of the direct and indirect band gaps occurs at 300 K for the (Al 0.58 Ga 0.42 ) 0.5 In 0.5 P material [11], which limits shorter-wavelength operation to about 555-570 nm and band-gap energies available for barrier and cladding materials [10]. Even for somewhat longer wavelengths, the higher active-region temperatures may lead to the considerable electron leakage (Fig.…”
Section: The Modelmentioning
confidence: 99%
“…There are three important features of the GaInP/ AlGaInP VCSELs which makes their high-temperature CW lasing operation more troublesome than in the case of standard GaAs/AlGaAs ones [10], smaller confining potential (shallower QWs), which means that the over-barrier carrier leakage will be greater, larger electron and heavyhole effective masses, which contributes to higher threshold currents, and too wide band-gaps of some structure layers, which may lead to a band-to-band absorption. Besides, higher carrier effective masses reduce efficiency of their injection into distant QWs, which limits their available numbers.…”
Section: The Modelmentioning
confidence: 99%
“…45 In the future, however, they could become the dominant type of laser diodes. 56 Recently, it has been reported that quantum dot semiconductor lasers show enhanced radiation hardness as compared with edge-emitting quantum well lasers. [57][58][59] Because this technology is very new, 60 little information is available.…”
Section: Improving the Radiation Hardness Of Laser Diodesmentioning
confidence: 99%